Profile of Occupational Dose at TRIGA 2000 Nuclear Facility - Rini Heroe Oetami; Afida Ikawati; Dadang Supriatna (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Occupational dose  is one of the safety parameters that must be verify to meet the safety objectives. Monitoring of occupational dose at TRIGA 2000 nuclear facility in 2015-2017 was performed using TLDs. The objectives of the monitoring were to evaluate and assess the occupational dose not to exceed the dose limit. In Technical and Health and Safety Division showed the maximum occupational dose for individual of 2.16 mSv and the highest collective dose of 0.029 man-Sv. The maximum occupational dose for individual in Reactor Division was of 1.48 mSv and the highest collective dose of 0.019 man-Sv. The maximum occupational dose for individual in Technophysic Division of 1.4 mSv and the highest collective dose of 0.017 man-Sv. In the Labeled Compound Division, the maximum occupational dose for individual of 2.59 mSv and the highest collective dose of 0.035 man-Sv  . From the total of 82 radiation workers, the highest percentage of radiation workers received the occupational doses in the dose range of (1.01-1.50) mSv were: 50% (41 persons, in 2015), 85.36% (70 persons, in 2016) and 70.73% (58 persons, in 2017). 4 persons dose record were within of (2.01-2.50) mSv and 2 persons within of (2.51-3.00) mSv. No radiation worker received doses exceeded the annual dose limit of 20 mSv. Keywords: Occupational dose, Equivalent dose, Dose limit, Radiation worker